Engagement in the Use of English and Chinese as Foreign Languages: The Role of Learner-Generated Content in Instructional Task Design - LAMBERT, CRAIG; ZHANG, GRACE (The Modern language journal (Boulder, Colo.), 2019)
This study investigates learner engagement in pedagogic task performance by triangulating multiple sources of data to gain insight into the cognitive and affective processes that take place on a range of tasks and how they engage learners of different target languages. The study provides a detailed analysis of 4 learners' second language (L2) performance (2 first language [L1] Japanese learners of English; 2 L1 Japanese learners of Chinese). All learners completed an identical set of 12 communication tasks in 3 discourse genres (instruction, narrative, and opinion) in a learner-generated (LGC) and teachergenerated content (TGC) condition. The performances were followed by immediate stimulated video recalls and questionnaires on perceived levels of anxiety and motivation during each task. Triangulation of these data sources revealed that both the English and Chinese learners were more socially and emotionally engaged in LGC tasks than in TGC tasks and that this engagement was associated with more fluent and accurate, but less complex, speech. The difference between the Chinese and English learners was in their self-reported preferences and levels of anxiety and motivation while performing the tasks in the respective conditions. Based on the learners' background profiles, this difference in subjective response to the tasks is attributed to previous experience with formal L2 instruction.